The Kidney-Related Effects of Polystyrene Microplastics on Human Kidney Proximal Tubular Epithelial Cells HK-2 and Male C57BL/6 Mice - Wang, Yung-Li; Lee, Yu-Hsuan; Hsu, Yung-Ho; Chiu, I-Jen; Huang, Cathy Chia-Yu; Huang, Chih-Chia; Chia, Zi-Chun; Lee, Chung-Pei; Lin, Yuh-Feng; Chiu, Hui-Wen (Environmental health perspectives, 2021)
Understanding the epidemic of chronic kidney disease of uncertain etiology may be critical for health policies and public health responses. Recent studies have shown that microplastics (MPs) contaminate our food chain and accumulate in the gut, liver, kidney, muscle, and so on. Humans manufacture many plastics-related products. Previous studies have indicated that particles of these products have several effects on the gut and liver. Polystyrene (PS)-MPs (PS-MPs) induce several responses, such as oxidative stress, and affect living organisms. The aim of this study was to investigate the effects of PS-MPs in kidney cells and . PS-MPs were evaluated in human kidney proximal tubular epithelial cells (HK-2 cells) and male C57BL/6 mice. Mitochondrial reactive oxygen species (ROS), endoplasmic reticulum (ER) stress, inflammation, and autophagy were analyzed in kidney cells. , we evaluated biomarkers of kidney function, kidney ultrastructure, muscle mass, and grip strength, and urine protein levels, as well as the accumulation of PS-MPs in the kidney tissue. Uptake of PS-MPs at different concentrations by HK-2 cells resulted in higher levels of mitochondrial ROS and the mitochondrial protein Bad. Cells exposed to PS-MPs had higher ER stress and markers of inflammation. MitoTEMPO, which is a mitochondrial ROS antioxidant, mitigated the higher levels of mitochondrial ROS, Bad, ER stress, and specific autophagy-related proteins seen with PS-MP exposure. Furthermore, cells exposed to PS-MPs had higher protein levels of LC3 and Beclin 1. PS-MPs also had changes in phosphorylation of mitogen-activated protein kinase (MAPK) and protein kinase B (AKT)/mitogen-activated protein kinase (mTOR) signaling pathways. In an study, PS-MPs accumulated and the treated mice had more histopathological lesions in the kidneys and higher levels of ER stress, inflammatory markers, and autophagy-related proteins in the kidneys after PS-MPs treatment by oral gavage. The results suggest that PS-MPs caused mitochondrial dysfunction, ER stress, inflammation, and autophagy in kidney cells and accumulated in HK-2 cells and in the kidneys of mice. These results suggest that long-term PS-MPs exposure may be a risk factor for kidney health. https://doi.org/10.1289/EHP7612.